2000
DOI: 10.15760/etd.1469
|View full text |Cite
|
Sign up to set email alerts
|

The structuring of procedures utilized in an adult stuttering treatment program

Abstract: In recent years. operant conditioning techniques have been effectively used to modify ~ variety of behaviors. For the most part, . , the modification of stuttering behavior has relied solely on the use of punishment. The shaping of "fluencyll through differential rein. ' forcement has been reported as a behavioral approach for the treat ment of stuttering; however, the effectiveness of this technique in combination with other "teaching" tools, such as, modeling, instruc tion, and explanation has not been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…score and/or greater overall fluency gain from baseline to follow-up. These data add some new information to the findings of numerous researchers (Shames, Egolf and Rhodes, 1969;Egolf, Shames and Blind, 1971;Prichard, 1971;and Culatta and Rubin, 1973) who suggest that the use of overall desirable language themes seems to play a major role in the establishment of fluency. Although this study seems to support a relationship between desirable language themes and maintained fluency improvements the degree of relationship is difficult to state conclu-sively at this point due to several uncontrolled variables which will be discussed later.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…score and/or greater overall fluency gain from baseline to follow-up. These data add some new information to the findings of numerous researchers (Shames, Egolf and Rhodes, 1969;Egolf, Shames and Blind, 1971;Prichard, 1971;and Culatta and Rubin, 1973) who suggest that the use of overall desirable language themes seems to play a major role in the establishment of fluency. Although this study seems to support a relationship between desirable language themes and maintained fluency improvements the degree of relationship is difficult to state conclu-sively at this point due to several uncontrolled variables which will be discussed later.…”
Section: Resultssupporting
confidence: 67%
“…The present research adds to that of others (Johnson, 1955;Williams, 1957;Shames, Egolf and Rhodes, 1969;Egolf, Shames and Blind, 1971;Prichard, 1971;Culatta and Rubin, 1973;and Casteel, 1976) who have found that there seems to be a relationship between fluency and language or thematics. While other research has indicated a relationship between the establishment of fluency and the use of desirable language during an intervention program, this research suggests that desirable language may also be related to overall clinical gain and fluency improvement that is maintained over an extended period of time.…”
supporting
confidence: 85%
See 3 more Smart Citations